HUBUNGAN LAMA PENGOBATAN ANTIPSIKOTIK DENGAN KEPATUHAN MINUM OBAT PADA PASIEN SKIZOFRENIA DI POLI PSIKIATRI PUSKESMAS REJOSO KABUPATEN NGANJUK - Cucuk Suwandi; Rosriyana Meilina Devi; Heru Wahyudi (LPPM STIKes SATRIA BHAKTI NGANJUK, 2020)
Schizophrenic patients should be through 6-12 month of treatment since the symptoms improve, but antipsychotic treatment should be maintained for 1-2 years to prevent relapse. The design of this research was correlation with cross sectional approach. Samples were taken by Accidental Sampling technique and obtained as 40 respondents. The independent variable waslong of antipsychotic’s treatment (medical record) and the dependent variable was medication adherence (questionnaire MMAS-8). This study indicate that most of the schizophrenic patients hadbeen duration of treatment more than of 12 months, as many as 22 respondents (55.0%). Most respondents of schizophrenic patients had been low medication adherence as many as 26 respondents (65%).Spearman Rank test results show that p-value = 0.000 <a (0,05) so that Ha accepted mean long antipsychotic treatment related to medication adherence on schizophrenic patients, with r = 0,783